Relação entre práticas pedagógicas multimodais e atenção conjunta na aquisição da linguagem: o que pensam docentes da educação infantil? - Lira, Mércia Duarte de (2021)
Official documents such as the Common National Curricular Base (BNCC) and the Pernambuco Curriculum advocate pedagogical work for early childhood education focused on play and interaction. In this sense, the aim of this research was to analyze the pedagogical practices reported by early childhood education teachers, in order to understand their impact on the establishment of joint attention with children in language acquisition. Thus, the theoretical contribution is based mainly on the contributions of McNeill (1985, 1992, 1997), Kendon (2009, 2016), Cavalcante and Brandão (2012), Fonte (2014), Fonte and Cavalcante (2016), Ávila Nóbrega (2018), Goldin-Meadow (2004), Bruner (1975, 1983) and Tomasello (2003; 2019). This study presents a qualitative approach from document analysis and action research. Data collection was carried out through semi structured interviews with Early Childhood Education teachers, who teach classes for five-year-old children, assigned to a public school in Ipojuca (PE). Knowledge about multimodality and multimodal practices for the establishment of joint attention were the focus of the interviews, conducted before and after lectures and workshops to see if there was variation in the teachers' multimodal knowledge and practices. The data collected showed that the conceptions presented by most of the interviewees about multimodality are different from the multimodal proposal advocated by authors such as Kendon and McNeill, who understand speech and gestures as linguistic and inseparable elements. Moreover, the guidelines of the official educational documents, by having play and interaction as the main axes, signalize pedagogical work that explores different linguistic manifestations of the student. As for joint attention, most of the teachers said they were unaware of this term, although they believe that other linguistic elements are complementary to share attention with students. After the lecture and workshops, most of the teachers understood language from a multimodal perspective, which led to the proposition of activities that explored the different language modalities as tools to share attention with students and engage them in the learning process.